What Does Deliberate Practice Have to Offer Mathematics? - Paukner, Lyle (My University, 2013)
Deliberate practice is a form of practice that consists of focused, repetitive practice of above-average difficulty. The subject continuously monitors his or her performance, and subsequently corrects, experiments, and reacts to immediate and constant feedback, with the aim of steady and consistent improvement. The purpose of this study was to discover practice techniques that encourage students to deliberately practice algebraic skills.
Color poster with text, graphs, images, and charts.
Keywords: Deliberate practice; Algebra; Posters